Beyond Tariffs and Quotas : Why Don't African Manufacturers Export More? - Clarke, George R.G. (World Bank, Washington, DC, 2012)
There has been much concern about Africa's recent export performance. Even though tariff and non-tariff barriers to trade have been falling, Africa's share of world exports has declined and most African countries remain highly dependent on a narrow range of primary commodities for export earnings. The author looks at factors that affect the export performance of manufacturing enterprises in eight African countries. In addition to enterprise characteristics (such as size, ownership, and education of the manager), policy-related variables also affect export performance. Manufacturing enterprises are less likely to export in countries with restrictive trade and customs regulation and poor customs administration. In contrast, there is less evidence that the quality of domestic transportation infrastructure has a large impact on export performance. Although the coefficient on this variable is negative, it is statistically insignificant in most model specifications.